Cosmetic Nanomaterials in Wastewater: Titanium Dioxide and Fullerenes - Pulicharla, Rama (2016)
The rapid growth in the cosmetic industry across the world is mainly due to the application of nanoingredients in cosmetics to enhance their properties and invention of new nanomolecules. Also, the weaker regulations on the application of nanoparticles as cosmetic ingredients and no safety assessment of cosmetics before release into the market has led to uncontrolled production and usage. Unavoidable release of a considerable amount of cosmetic nanoparticles into wastewater introduces them into the environment via treated wastewater effluent and sludge. This paper briefly gives the information about behavior of cosmetic nanomaterials, mainly titanium dioxide (TiO2TiO2) and fullerenes (C60), within the wastewater-treatment plant and current research on their characterization and toxicity. Considering the current analytical methods for evaluating the behavior of these nanomaterials in the wastewater, there is still a need to advance these technologies. Furthermore, a better understanding and modeling of nanomaterials’ fate in wastewater-treatment plants is essential for effectively predicting their impacts on the receiving environment.